Quality of life among pediatric and adolescent patients with migraine: A cross-sectional study - Ahmed K. Bamaga; Lama Alqarni; Mariya Ibrahim Alrefaei; Hind Zayed Aljedani; Khlod Ahmad Ywsef; Hadeel Hamzah Yaseen; Kholood Rasdwi; Yosra Khalil Alhuzaifi (Journal of Family Medicine and Primary Care)
Introduction: Migraine can occur at any stage of childhood; however, its prevalence increases during school years, affecting various aspects of life, including daily routines and school attendance. Objective: To evaluate the quality of life (QOL) in children and adolescents with migraines. Methods: This cross-sectional study was conducted at several specialized pediatric neurology clinics between 2020 and 2023. Participants were provided with an online questionnaire. The validated Pediatric Quality of Life Inventory (PedsQL) for parental reports was applied to evaluate QOL, covering four dimensions: physical, emotional, social, and school functioning. Results: In total, 109 eligible patients were identified, yielding an estimated prevalence of 5.45%. The study population comprised 51% males, with a mean age of onset of 9 ± 3 years. The mean total PedsQL score across all dimensions per participant was 76 ± 17 points. Significant associations were observed for age (P = 0.02), adherence to dietary recommendations (P = 0.01), and hours spent playing video games per day (P = 0.02) on the total PedsQL score. Conclusion: Children and adolescents with migraines exhibit a reduced QOL, particularly in the emotional and school functioning domains. These findings underscore the importance of early screening and management of migraines in pediatric patients.